Accretion, subduction erosion, and tectonic extrusion during late Paleozoic to Mesozoic orogenesis in NE China. (1st June 2020) - Aouizerat, Arthur; Xiao, Wenjiao; Schulmann, Karel; Windley, Brian F.; Zhou, Jianbo; Zhang, Jinjiang; Ao, Songjian; Song, Dongfang; Monie, Patrick; Liu, Kai
Graphical abstract: Highlights: Periods of accretionary growth happened between 305 Ma-195 Ma and 112 Ma-101 Ma. A period of subduction erosion affected the Songliao Block from 195 Ma to 142 Ma. The Jiamusi and Songliao Blocks were together amalgamated in the early Cretaceous. A Jurassic-early Cretaceous extrusion event disturbed the orogenic architecture. Abstract: The high-pressure Heilongjiang Complex records a long and complicated evolution from the late Paleozoic to Mesozoic in NE China, which is still subject to controversy. In this paper we present a new detailed study including structural, geochemical and geochronological analyses (Ar–Ar dating on metamorphic minerals, U-Pb SIMS dating on zircons). Two main periods of oceanward accretionary growth are identified between 305 Ma and 195 Ma and around 112–101 Ma. These periods of accretionary growth were associated with the emplacement of voluminous magmatism, slab roll-back with continental back-arc extension, and growth of a forearc accretionary prism. Between these periods of accretionary growth, a major phase of regional subduction erosion took place between 195 Ma and 142 Ma at the eastern edge of the Songliao Block. The main effects of this subduction erosion phase were that regional Jurassic-early Cretaceous extrusion overlapped with Mesozoic accretion and erosion in NE China, which disturbed the initial orogenic architecture. With a review of relevant zircon ages of this accretionary orogen, we unravel the complicated geodynamic history of accretion, subduction erosion and tectonic extrusion that shaped NE China from the late Paleozoic to Mesozoic.